PEMBERDAYAAN KOMUNITAS UMKM KAMPUNG GEMPLAKAN ATAS MELALUI STRATEGI DIGITALISASI DALAM KOMUNIKASI PEMASARAN DAN BRANDING PRODUK JAMBUKU - Bernadhed Bernadhed; Mulia Sulistiyono; Nurfian Yudhistira (Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to the national economy but continue to face limitations in digital literacy, marketing communication strategies, and brand consistency. Jambuku MSME in Gemplakan Atas Village is a community-based enterprise focusing on guava-based products with promising economic potential, yet its market reach remains limited due to the lack of digital adoption. This community service program aimed to enhance partner capacity through training in digital marketing, product photography and videography, digital content production, professional content creation, and the utilization of a business profile website. The method included initial observation, program planning, five training sessions, technical assistance, and evaluation using pre-test, post-test, and field monitoring. Results indicated an average improvement of 35% in participants’ understanding, with the highest gain observed in digital marketing and branding. Outputs included improved visual communication quality, consistent content publication, and the use of a website as a digital product catalog. Overall, the program demonstrates that integrated digitalization is an effective strategy for empowering MSMEs to increase competitiveness and expand market access.